2011
DOI: 10.3382/ps.2010-01301
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the growth pattern of in-season and off-season Ross 308 broiler breeder flocks

Abstract: Growing the Ross broiler parent according to the target growth curve ensures that males and females achieve optimum lifetime performance and well-being. Accurate control of growth will lead to uniformity and sexual maturity, which are of crucial importance for the production of hygienic, healthy, and fertile eggs of high quality. This study examined the growth of Ross 308 broiler breeder flocks from hatch to 35 wk of age to identify which growth model would describe the growth of these animals most accurately.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…In agreement with this finding, the superiority of the Richards function, for its ability to function the growth curve of broiler chickens (male and female) and Ross 308 broiler parent flocks has been reported by other researchers (Darmani Kuhi et al, 2003;Tompić et al, 2011).…”
Section: Discussionsupporting
confidence: 74%
“…In agreement with this finding, the superiority of the Richards function, for its ability to function the growth curve of broiler chickens (male and female) and Ross 308 broiler parent flocks has been reported by other researchers (Darmani Kuhi et al, 2003;Tompić et al, 2011).…”
Section: Discussionsupporting
confidence: 74%
“…Tompić et al (2011) obtained the best adjustments using the Richards and Gompertz growth models in broilers; Yang et al (2006) reported the von Bertalanffy model as the most accurate in Jinghai Yellow chicken; and Eleroğlu et al (2014) had concluded that the Logistic model the best fit in growth of slow performance chickens. However, despite the variety of existing growth models, one of the most recommended ones has been the Gompertz model in its traditional form (Freitas, 2005;Mazucheli et al, 2011;Drumond et al, 2013;Mohammed, 2015;Mota et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Richards (1) Gompertz, Logistic, and von Bertalanffy were adapted from Freitas (2005); while Richards was adapted from Tompić et al (2011). A, asymptotic final bodyweight; B, integration constant; K, maturity rate; M, (-1/n), i.e., the parameter that gives the curve its form; and, the residue in time t.…”
Section: Methodsmentioning
confidence: 99%
“…It is an important characteristic that describe the genetic potential of an individual. Growth can be defined as the development of body size per time unit or also called as growth rate (Tompić et al 2011). Based on the rate, the growth is divided into two phases: acceleration and retardation phases.…”
Section: Introductionmentioning
confidence: 99%